Duration of delayed graft function and its impact on graft outcomes in deceased donor kidney transplantation - Pooja Budhiraja; Kunam S Reddy; Richard J Butterfield; Caroline C Jadlowiec; Adyr A. Moss; Hassan A Khamash; Lavanya Kodali; Suman S Misra; Raymond L Heilman (BMC Nephrology, 2022)
Abstract Background There is controversy regarding the impact of delayed graft function (DGF) on kidney transplant outcomes. We hypothesize that the duration of DGF, rather than DGF itself, is associated with long-term kidney graft function. Methods We analyzed all deceased donor kidney transplants (DDKT) done at our center between 2008 to 2020. We determined factors associated with DGF duration. DGF duration was assessed at three 14-day intervals: < 14 DGF days, 14–27 DGF days, > 28 DGF days. We studied the impact of DGF duration on survival and graft function and resource utilization, including hospital length of stay and readmissions. Results 1714 DDKT recipients were included, 59.4% (n = 1018) had DGF. The median DGF duration was 10 days IQR (6,15). The majority of recipients (95%) had resolution of DGF within 28 days. Donor factors associated with DGF days were longer cold ischemia time, donor on inotropes, older age, donation after circulatory death, higher terminal creatinine, and hypertension. Recipient factors associated with increased DGF duration included male sex, length on dialysis before transplant, and higher body mass index. There were no differences in acute rejection events or interstitial fibrosis progression by 4 months when comparing DGF days. The median length of stay was 3 days. However, readmissions increased with increasing DGF duration. Death-censored graft survival was not associated with the length of DGF except when DGF lasted > 28 days. Conclusions Inferior graft survival was observed only in recipients of DDKT with DGF lasting beyond 28 days. DGF lasting < 28 days had no impact on graft survival. Duration of DGF, rather than DGF itself, is associated with graft survival. Trial Registration Retrospective study approved by Mayo Clinic IRB number ID: 20-011561.